CALCULATION OF VALUE OF OVERALL EQUIPMENT EFFECTIVENESS AS A BASIS OF PRODUCTIVITY IMPROVEMENT PROCESS SHEARING LEAF SPRING IN PT INDOSPRING TBK GRESIK - Suparno Suparno; Imam Bahroni (UNIPA PRESS, 2019)
PT. Indospring, Tbk as a motor vehicle producer industry is demanded to continuously improve the quality of products made in order to remain competitive in the current era of globalization. This is in line with the amount of demand that shows an upward trend. However, the performance of one of the production equipment that is not running optimally causes the output of production is low. From this problem, how is the OEE measurement as the basis of the proposed improvement design to improve the performance of the production equipment so as to achieve World Class Value standard.In performing these performance improvements, it is used OEE method application, Fishbone Diagram, Pareto Diagram in solving the problems that occur. OEE calculation results show that the equipment in the Eye Forming Process has the lowest OEE value compared to Cutting and Process Punching that is equal to 77.94%. This is due to 2 factors namely Performance Factor (83.83%) and Quality Factor (96.18%). The result of analysis that the biggest factor of Performance (Unplanned Down Time) is the first because the process of set up is 733 minutes (52,47%) and secondly because the problem of mandril jam is 450 minutes (32,21%) and Eye Forming Defect ), The first is Eye forming Deformed 1034 pcs (60.50%) and the second is Eye forming Defect Grip as much as 381 pcs (22.29%). Based on the results of the analysis then made an improvement proposal based on the priority of critical problems that occur to improve the performance of equipment in the process.